Pembinaan Teknik Berpidato dalam Meningkatkan Kreatifitas Santri - Saifudin, Ahmad; Sumanan, Sumanan; In?am, Asichul (Janaka, Jurnal Pengabdian Masyarakat, 2020)
The mission of Da'wah in Islamic educational institutions such as the Al-Qur'an Education Park demands the supply of learners to have adequate verbal communication skills. Verbal stimulation is necessary to provide an understanding of the importance of reactualization of speech ability in order to ensure the success of Da'wah. In the context of the Qur'an Education Park requires assistance in obtaining an integral stakeholder empowerment vehicle. Through the approach of assets and resources mentoring speech exercises as a verbal stimulation in the education Park Al-Qur'an at-Taqwa Sumberejo Lengkong Nganjuk produces the ability to empower assets and potential managers and key figures. Performance can be fulfilled because it is supported by the effectiveness of social sales, planning with partner devotion, implementation of programs involving assets and potential and role of key figures in the control function.